E-business, innovation and SMEs: the significance of hosted services and firm aggregations. (29th January 2007) - Brown, David H.; Lockett, Nigel
Against a background of the low engagement of Small- to Medium-sized Enterprises (SMEs) in e-business this paper investigates the significance of hosted services and firm aggregations. On the basis of qualitative case studies of aggregations of SMEs, the research shows how e-business-based innovation can occur, and identifies the extent to which the aggregation factor contributes to this innovation. The research confirms existing understanding of the importance of network-based aggregations but adds to this with further detail and examples, including the 'outsourcing' of innovation to the Application Service Providers (ASPs).